1984
DOI: 10.3406/arsci.1984.1210
|View full text |Cite
|
Sign up to set email alerts
|

La stabilité des céramiques par rapport à l'environnement

Abstract: Cette étude sur la stabilité des céramiques par rapport à leur environnement a été élaborée dans le but d'évaluer les changements dans la composition en éléments-traces des céramiques qui se sont conservées et qui, par ailleurs, ne présentent pas de signes de détérioration physique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Freestone et al (1985), Walter and Besnus (1989) and Freestone (2001) argued that phosphates can precipitate in potsherds from aqueous solutions, forming sub-microscopic crystals and thin films, or adsorb at the surface of primary mineral phases, leading to high bulk phosphorus, a parameter that is commonly assumed to be a marker for contamination. The experimental work of Vitali et al (1984), Franklin and Vitali (1985) and Collomb and Maggetti (1996) supports this mechanism for phosphorus enrichment in potsherds. In soils, phosphate precipitation is related to environmental conditions, particularly to pH and Eh (Nriagu and Dell 1974;Lindsay and Vlek 1977), which are controlled by a complex interaction of changes in the water table, movement of water in the ground (Medrano and Piper 1997;Ann et al 2000;Pierri et al 2000;Scaccia et al 2002), the presence of organic matter and bacterial activity (Fredrickson et al 1998;Brown et al .…”
Section: Discussionsupporting
confidence: 53%
“…Freestone et al (1985), Walter and Besnus (1989) and Freestone (2001) argued that phosphates can precipitate in potsherds from aqueous solutions, forming sub-microscopic crystals and thin films, or adsorb at the surface of primary mineral phases, leading to high bulk phosphorus, a parameter that is commonly assumed to be a marker for contamination. The experimental work of Vitali et al (1984), Franklin and Vitali (1985) and Collomb and Maggetti (1996) supports this mechanism for phosphorus enrichment in potsherds. In soils, phosphate precipitation is related to environmental conditions, particularly to pH and Eh (Nriagu and Dell 1974;Lindsay and Vlek 1977), which are controlled by a complex interaction of changes in the water table, movement of water in the ground (Medrano and Piper 1997;Ann et al 2000;Pierri et al 2000;Scaccia et al 2002), the presence of organic matter and bacterial activity (Fredrickson et al 1998;Brown et al .…”
Section: Discussionsupporting
confidence: 53%
“…This research found that for all but the coarsest of wares, all elements that were measured relatively precisely could be analysed quite reliably using either 100 mg or 300 mg samples. A study of surface corrosion of newly made ceramics was one of the first such laboratory studies (Vitali et al 1984; Franklin and Vitali 1985).…”
Section: Numbers Of Archaeological and Historical Samples Analysedmentioning
confidence: 99%